Enhancing Trust, Internal Control, and Accountability: Budget Goals Commitment as a Mediator - Rudiyanto Rudiyanto; Zakiyya Tunnufus; Ela Widasari (Owner : Riset dan Jurnal Akuntansi, 2025)
We investigated the effects of trust in supervisors (TS), internal control (INCTRL), and budget goals commitment (BGC) on public performance accountability (PERFACT). Using data collected from 191 respondents through structured questionnaires, the research verifies the direct and indirect relationships between variables based on structural equation modeling (SEM) analysis. Our evidences reveal that in the first structural model, trust in supervisors and internal control significantly influence budget goals commitment, with trust in supervisors being significant. This highlights the critical role of fostering trust to ensure stronger commitment to budgetary objectives. In the second structural model, public performance accountability is significantly influenced by internal control and budget goals commitment. Although trust in supervisors has less of a direct impact on public accountability, indicating that its effect may be more nuanced and indirect. Furthermore, the study provides empirical evidence for the mediating role of budget goals commitment. Specifically, it demonstrates that budget goals commitment bridges the relationship between trust in supervisors and public accountability. This finding underscores the importance of a committed budgetary framework in enhancing accountability in public sector organizations. This relationship is highlighted by practitioners and policy makers as meaningful knowledge and insight. Strengthening internal control systems and fostering trust in supervisors, combined with a focus on budget goals commitment, can significantly enhance public performance accountability.